Towards national health insurance: Alignment of strategic human resources in South Africa - Nathaniel Mofolo; Christo Heunis; Gladys N. Kigozi (AOSIS, 2019)
Background: South Africa is implementing national health insurance (NHI) and primary health care (PHC) re-engineering, and has concomitantly introduced the Human Resources for Health (HRH) Strategy. These policies are underpinned by the National Development Plan (NDP), which aims to address widespread inequality and inequity. Aim: The aim of this study was to analyse the alignment of national HRH-related policies to implement NHI and PHC re-engineering and determine knowledge gaps and research needs. Method: A narrative review of the NDP, PHC re-engineering, HRH and NHI strategies was carried out, supplemented by key HRH reports, data and articles. Results: Current policies stress NHI and PHC re-engineering without effectively addressing shortages and maldistribution of HRH across the provincial and public-private divides. In line with PHC re-engineering, the HRH Strategy emphasised strengthening of community health workers (CHWs), professional nurses (PNs), mid-level workers (MLWs), medical practitioners (MPs) and clinical specialists (CSs). Four of these, CHWs, MLWs, MPs and CSs, are varyingly still in absolute shortfall, as well as being inequitably distributed across the provincial and public-private divides. The seeming adequacy in the absolute number of PNs may disguise provincial and public-private sector disparities. Although expedited HRH development and equitable deployment are crucial, it is also vital to resolve extant education and accreditation challenges delaying HRH policy implementation. Conclusion: The current lack of alignment of HRH policies does not portend well for the successful implementation of NHI and PHC re-engineering. Knowledge gaps include the need for further clarification of ideal multi-disciplinary team compositions and responsibilities.